Key European guidelines for the diagnosis and management of patients with phenylketonuria - Spronsen, F. J. van; Blau, Nenad; Trefz, Friedrich K. (The lancet. Diabetes & Endocrinology, 2017)
Summary: We developed European guidelines to optimise phenylketonuria (PKU) care. To develop the guidelines, we did a literature search, critical appraisal, and evidence grading according to the Scottish Intercollegiate Guidelines Network method. We used the Delphi method when little or no evidence was available. From the 70 recommendations formulated, in this Review we describe ten that we deem as having the highest priority. Diet is the cornerstone of treatment, although some patients can benefit from tetrahydrobiopterin (BH4). Untreated blood phenylalanine concentrations determine management of people with PKU. No intervention is required if the blood phenylalanine concentration is less than 360 μmol/L. Treatment is recommended up to the age of 12 years if the phenylalanine blood concentration is between 360 μmol/L and 600 μmol/L, and lifelong treatment is recommended if the concentration is more than 600 μmol/L. For women trying to conceive and during pregnancy (maternal PKU), untreated phenylalanine blood concentrations of more than 360 μmol/L need to be reduced. Treatment target concentrations are as follows: 120-360 μmol/L for individuals aged 0-12 years and for maternal PKU, and 120-600 μmol/L for non-pregnant individuals older than 12 years. Minimum requirements for the management and follow-up of patients with PKU are scheduled according to age, adherence to treatment, and clinical status. Nutritional, clinical, and biochemical follow-up is necessary for all patients, regardless of therapy.
Available online 10 January 2017
Gesehen am 27.09.2018